Interest based micro-credit is a problem for women entrepreneurs: considering murabaha financing as an alternative in the light of Maqasid Al-Shari'ah - Mohammed Shehu, Farida; Ahmad, Nor Hayati; Al-Aidaros, Al-Hasan (2019)
Microfinance banks are established to cater for the needs of the economically active poor majority of whom are women. From its evolution, there have been controversies about its impact and growing concern, about its products and services from the Islamic perspective. The products and services of the microfinance banks are majorly based on Riba (interest) and Islam strongly condemns any form of dealings with Riba. The charging of interest by microfinance banks has resulted in an overall high cost of borrowing for the women entrepreneurs. The objective of this paper is to investigate, through literature review, whether interest based micro-credit is a problem to the business performance of women entrepreneurs. The exploratory study adopting content analysis, to achieve its aim, found that charging interest on borrowed money is a key obstacle for women entrepreneurs. As such, the paper proposed an alternative to interest based micro-credit (i.e., murabaha financing [cost-plus]) in the light of Maqasid Al-Shari’ah.